The Impact of the COVID-19 Pandemic on the Physical Fitness of Primary School Students in China Based on the Bronfenbrenner Ecological Theory - Li, Hailing; Cheong, Jadeera Phaik Geok (Frontiers in Psychology, 2022)
After the outbreak of the COVID-19 pandemic, nation lockdown became an effective way to isolate the spread of the virus. Schools were postponed, students had to stay at home and opportunities for physical activity amongst school children were severely affected. This research sought to determine the impact of the pandemic on the physical fitness of primary school students. In total, 1235 students from grades one to five in a primary school in Beijing took part in this research. Using the Chinese National Student Physical Fitness Standard as a guide, the students were subjected to BMI, vital capacity, 50m sprint, sit and reach, timed rope-skipping, timed sit-ups, and 50m×8 shuttle run measurements. These tests were administered once before and once after the lockdown period. The results showed that the overall physical fitness of the participants was better after the lockdown (p<0.05, r= -0.14). Specifically, vital capacity, sit and reach, timed rope-skipping and timed sit-ups had improved after the lockdown. Meanwhile, 50m×8 shuttle run dropped slightly but not significantly whereas 50m sprint dropped sharply after the lockdown. The proportion of overweight and obese students increased, but the difference before and after the lockdown was small. It appeared that during the pandemic, through the intervention of many comprehensive factors, home-based fitness was normalized and promoted the healthy development of students.